Challenges for the electric mobility transition: lessons from Norway and perspectives for Brazil - Silva, Júlia Febraro França Gomes da (2019)
This study provides an in-depth analysis of the process of electric mobility transition by using two case studies – Norway and Brazil. From a socio-technical perspective, it explores the interaction between technology and society, and proposes adapted multi- level perspective (MLP) models to each country as tools for analyzing the two different contexts of technological transition. The models account for urban trends as relevant drivers in electric mobility transitions, contributing to fill a gap in the literature related to the lack of empirical support on the importance of spatial scales in sustainability transitions analyses. Following a pathway case strategy, a particular focus is given on the causal mechanisms of electric mobility transition in both cases. The aim is to investigate whether the instruments adopted in Norway – one of the world’s most advanced market for electric vehicles – would also be potentially effective in Brazil. The study concludes that the instruments adopted in Norway, responsible for overcoming the challenges for a successful transition, would most likely not be effective in the Brazilian context. The promising pathway for the introduction of electric vehicles in Brazil would be either by the electrification of public transportation, especially buses, and/or the hybridization strategy, through the development of the hybrid flex fuel technology.